(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
This article presents some reflections on the paths for vocational guidance in the Costa Rican educational system. It reflects on the complexity of the contexts within which guidance is circumscribed and on the need to establish professional practice on a paradigm of complexity. This position will allow for timely responses to the challenges inherent to professional practice, so that these are addressed with a broad and dynamic perspective that considers the complex framework that characterizes the person being guided based on political, economic, social, cultural, and axiological circumstances, as well as their interrelations and perceptions. At the same time, it revisits some elements of the life designing approach, which allows vocational guidance intervention to be operationalized from a perspective of complexity, by proposing the need to move towards a model adapted to current realities that consider the context, values, interrelations, perceptions, and personal capacities in the construction of trajectories in the different areas of life. Finally, some key points are proposed for optimizing vocational guidance, ensuring that the guiding actions are rooted in the substantial elements proposed by both theoretical perspectives. The goal is to enhance employability, career development, and social justice for the target populations served.